The circles of care game © - using gaming to teach interprofessional teamwork in clerkship. Issue 1 (2nd January 2020) - Chan, Adrian; Fung, Kevin; Orchard, Carole
ABSTRACT: The aim of this study was to gain insight into how online gaming can teach medical students about interprofessional collaborative practice and promote their development of interprofessional competencies prior to clerkship. This prospective cohort study involved third year medical students from the Schulich School of Medicine and Dentistry in London, Ontario, Canada who participated in the 'Circles of Care'© online board game. A total of 97 student reflections were obtained and subjected to conventional qualitative descriptive content analysis. The transcribed data were analyzed question by question and line by line. Themes evolved from four questions: (1) What surprised you the most about teamwork from this learning activity, (2) What did you learn about collaborative teamwork, (3) What will you take away from this learning event to use in your practice, and (4) Please comment on the value of using a game such as this one to develop your collaborative team practice. A total of seven themes emerged including: "Gaining insights", "What worked and what did not", "Openness to learning", "Comfort in sharing with others", "Commitment and skepticism", "Being a seeker", and "Continuum of value to learning and practice". Analysis of the student reflections illustrated the potential of using an online-based game to effectively introduce and teach interprofessional competencies to medical students.